Pour une littérature-monde en français : les limites d'un discours utopique - Porra, Véronique (2018)
: In March 2007, the French daily newspaper Le Monde published a manifesto by French-speaking writers, calling for the advent of a « littérature monde » in French, thus triggering off a polemic, affecting both literary and political circles. However, a detailed analysis of the discourses within and revolving around this initiative, presented as revolutionary, shows to what extent it is rather involved in the complexity of preceding debates. The decentering of perspectives, the liberation of forms and the end of the pact between language and the nation therefore seem to be laudable aspirations indeed, but, in the context of the functioning of the francophone literary system, they fundamentally belong to the anhistorical and utopian discourses.